Retirement dynamics and anticipated well-being: insights from rural Vietnam - Dai Binh Tran; Pham Ngoc Tham; Pablo Barriga (Humanities & Social Sciences Communications)
Abstract As populations age, ensuring well-being in retirement becomes increasingly important. This study examines the relationship between retirement and anticipated well-being in rural Vietnam, utilizing data from the Thailand-Vietnam Socio-Economic Panel (TVSEP) and an instrumental variable approach. The findings indicate that retirement has a negative impact on anticipated well-being, with significant differences across gender and ethnic groups. Particularly, this effect is statistically significant only among women and individuals of the Kinh ethnicity. These results emphasize the need for targeted social programs that consider socio-demographic characteristics to improve the future welfare of elderly populations. By providing insights into retirement dynamics in developing countries, our study offers valuable guidance for policymakers striving to enhance well-being, reduce gender disparities, and ensure fairness in retirement outcomes within Vietnam’s rural communities.